Vietnam War primary sources - Hillstrom, Kevin (U.X.L Vietnam war reference library, 2001)
Beginning with a timeline, a "Words to Know" section, and a "Research and Activity Ideas" section, this book presents thirteen full or excerpted documents from the Vietnam War era, ranging from notable speeches that mark important points in the conflict to personal diaries and letters.